Author Correction: Efficient Generation of Mice with Consistent Transgene Expression by FEEST. Issue 1 (December 2018) - Gao, Lei; Jiang, Yonghua; Mu, Libing; Liu, Yanbin; Wang, Fengchao; Wang, Peng; Zhang, Aiqun; Tang, Nan; Chen, Ting; Luo, Minmin; Yu, Lei; Gao, Shaorong; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.